2020
DOI: 10.1101/2020.03.26.009803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The potential SARS-CoV-2 entry inhibitor

Abstract: Outbreak of coronavirus disease 2019 occurred in Wuhan and has rapidly spread to almost all parts of world. In coronaviruses, the receptor binding domain (RBD) in the distal part of S1 subunit of SARS-CoV-2 spike protein can directly bind to angiotensin converting enzyme 2 (ACE2). RBD promote viral entry into the host cells and is an important therapeutic target. In this study, we discovered that theaflavin showed the lower idock score (idock score: −7.95 kcal/mol). To confirm the result, we discovered that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…6), strongly suggesting that these catechin derivatives may interact with RBD of S protein to prevent viral attachment to ACE2 on the cell surface. Our results are not consistent with previous in silico docking simulation studies that suggested high affinity binding of EGCG and non-galloylated theaflavin to RBD 11,12 .…”
Section: Discussioncontrasting
confidence: 99%
“…6), strongly suggesting that these catechin derivatives may interact with RBD of S protein to prevent viral attachment to ACE2 on the cell surface. Our results are not consistent with previous in silico docking simulation studies that suggested high affinity binding of EGCG and non-galloylated theaflavin to RBD 11,12 .…”
Section: Discussioncontrasting
confidence: 99%
“…specifically reported on theaflavin-3,3’-digallate as an inhibitor of serine protease NS2B-NS3 of the Zika virus [ 43 ]. Moreover, it was found from in silica study that theaflavins have a high binding affinity (i,e., ΔG of −8.53 kcal/mol) to the RBD of SARS-CoV-2 through forming hydrophobic interactions along with hydrogen bonds at ARG454, PHE456, ASN460, CYS480, GLN493, ASN501, and VAL503 of RBD-SARS-CoV-2, in proximity of the ACE2-spike protein contact area [ 44 ]. Also, Maiti and Banerjee reported that theaflavin gallate prevents the RBD spike protein from binding to the hACE2 receptor [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also a well-known fact that their adequate intake may help to modulate immune responses and resistance to infection. The efficacy of polyphenols as antiviral compounds has been frequently reported, and there is an enormous potential in exploring their antiviral properties, since they are commonly recognized as safe and effective in substituting for, or in serving as an adjunct treatment to, conventional therapies [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Although, there is already substantial information about polyphenols' activity against SARS-CoV-2, most of these results are derived from computational modeling and computational predictions, and their capability as anti-SARS-CoV-2 agents still needs to be scientifically and clinically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The effective flavonoids found in this study can be ordered as follows affinity hesperidin > rutin > diosmin > apiin > diacetylcurcumin ( Adem et al, 2020 ). Lung et al (2020) in the computational study evaluated the potential of theaflavin. The theaflavin showed a high docking score with good binding with the RBD in SARS-CoV-2.…”
Section: Computational Approaches For Identification Of Targetmentioning
confidence: 99%
“…The driving forces of these interactions were hydrophobic interactions with hydrogen bonds at sites such as ARG454, ASN460, ASN501, GLN493, PHE456, CYS480, and VAL503 of SARS-CoV-2 RBD, near the ACE2-S protein. For the utmost promising interaction of theaflavin with the RBD in SARS-COV-2, the binding energy was found to be −8.53 kcal/mol ( Lung et al, 2020 ). In a molecular docking study, Shree et al (2020) worked to identify the SARS-COV-2 Mpro (Main protease) inhibitors.…”
Section: Computational Approaches For Identification Of Targetmentioning
confidence: 99%